Utopia in the anthropocene a change plan for a sustainable and equitable world - Harvey, Michael 1952- (Routledge studies in sustainability, 2019)
Utopia in the Anthropocene takes a cross-disciplinary approach to analyse our current world problems, identify the key resistance to change and take the reader step by step towards a more sustainable, equitable and rewarding world. It presents paradigm-shifting models of economics, political decision-making, business organization and leadership and community life. These are supported by psychological evidence, utopian literature and inspirational changes in history.The Anthropocene is in crisis, because human activity is changing almost everything about life on this planet at an unparalleled pace. Climate change, the environmental emergency, economic inequality, threats to democracy and peace and an onslaught of new technology: these planetwide risks can seem too big to comprehend, let alone manage. Our reckless pursuit of infinite economic growth on a finite planet could even take us towards a global dystopia. As an unprecedented frenzy of change grips the world, the case for utopia is stronger than ever. An effective change plan requires a bold, imaginative vision, practical goals and clarity around the psychological values necessary to bring about a transformation. This book will be of great interest to students and scholars of the environmental humanities, sustainability studies, ecological economics, organizational psychology, politics, utopian philosophy and literature - and all who long for a better world